ANALISIS MOTIVASI DAN HASIL BELAJAR PESERTA DIDIK PADA PEMBELAJARAN DARING SELAMA MASA PANDEMI COVID-19 - Nur Amaliah; Hastuti Oktari; Phika Ainnadya Hasan; Masyitha Wahid (JURNAL BIOEDUKASI, 2022)
SMAN 1 Tinambung is one of the schools that implemented online learning during the covid-19 pandemic. This study aims to analyze the motivation and learning outcomes of students in online learning during the Covid-19 pandemic in class XI MIA 1 at SMAN 1 Tinambung. This type of research is descriptive qualitative using a case study design. Research data was collected through observations, interviews and learning outcomes documents. The results of the study show that students' learning motivation during online learning can be said to be quite good during the pandemic, especially in class XI MIA 1 SMA Negeri 1 Tinambung, Polewali Regency. This can be seen in all students who always take part in the online learning process using the WhatsApp application. Students like the application because it is one of the most commonly used social media applications. Students also always do the assignments given by the teacher. As for the learning outcomes of class XI MIA 1 students during the online learning process, there were 6 students in the medium category (16.6%), and 30 students in the high category (83.4%). Students who have good learning motivation will produce much better learning outcomes than students who have less learning motivation.